Gênero e habilidades sociais: efeitos sobre a percepção do desempenho profissional - Nasser, Maria Clara Barbosa Brito Guimarães (Universidade Federal de São Carlos, 2022)
Differentiated perceptions of the work-related social skills of male and female managers may affect assessments of their professional competence. Moreover, gender-related differences may be more intense in fields where there is a significantly higher percentage of men than women. Thus, the aim of the present study was to compare the perception of the social behavior of male and female managers in two fields of work, in a context related to work-life balance. The study design involved four independent groups, considering two factors: professional field (law or IT) and gender of the manager (male or female). Four versions of a fictional scenario were created, modifying only the name of the manager (Paulo or Paula) and the initial contextualization of the situation. considering the fields of law and IT. There were 40 participants (21 men and 19 women), between the ages of 20 and 39, with exactly half from each professional field. After presenting one of the versions of the fictional scenario, an interview was conducted with each participant to obtain their quantitative and qualitative evaluations of the manager’s work-related social behavior. An analysis of variance (ANOVA) was used to evaluate the interaction effect for gender and professional field. No such effects were found, so considering the small number of participants, t-tests were used to examine the effects of each factor, separately. Content analysis was used to examine the justifications for the scores given for the manager’s performance. As main results, evaluations of the "overall performance" of the manager (on a scale from 1 to 10), tended to be lower among participants from the field of law (M = 4.95, SD = 2.17) than among the IT respondents (M = 6.15, DP = 2.23), t(38) = 1.73, p = 0.092, with a moderate effect size (g = 0.53). In their justifications for this score, the participants indicated the manager’s lack of dialogue with the team and unilateral decision-making. Furthermore, Paula received more critical comments than Paulo. When evaluating the "division of tasks", a difference based on gender was observed. Paulo was evaluated more negatively (M = 4.3, SD = 2.87) compared to Paula (M = 6.2, SD = 2.17), t(35) = 2.364, p = 0.024, with a moderate effect size (g = 0.73). Although Paula had higher evaluations than Paulo, she also received a greater number of criticisms for not having consulted the opinion of the team at the time of decision making. Thus, even when she obtained a higher score, she still received more servere comments about her behavior, which also confirms the expectation that there would be differences related to sex in the perception of the work-related social behavior of managers. Moreover, it was noted that a hierarchical organizational culture versus a team work approach seems to affect the interpretation of managers’ behavior. As methodological contributions, we highlight the creation of a fictional scenario that was evaluated as representative of the professional contexts investigated, in addition to the importance of combining quantitative and qualitative analyses. As a limitation, the sample size was small for statistical analyses. In future studies, it would be interesting to evaluate interventions that aim to help people notice the similarities in the interpersonal performance of managers of each sex, examining post-intervention effects on how often people criticise these managers.
The effects of gender and social skills on perceptions of work performance
Keywords: Gênero; Habilidades sociais; Desempenho profissional; Equilíbrio trabalho-vida; Gender; Social skills; Work performance; Work-life balance; CIENCIAS HUMANAS::PSICOLOGIA; CIENCIAS HUMANAS::PSICOLOGIA::PSICOLOGIA DO TRABALHO E ORGANIZACIONAL::FATORES HUMANOS NO TRABALHO; CIENCIAS HUMANAS::PSICOLOGIA::PSICOLOGIA SOCIAL::RELACOES INTERPESSOAIS